PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN PAKAN FERMENTASI AZOLLA PADA PETERNAK ITIK PETELUR DESA TANAH PRIUK KABUPATEN MUSI RAWAS - Karyono, Teguh; Safriyan, Etty; Murniati, Nely (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Feed is one of the important factors that play a role in livestock farming, 60%-70% of the production cost is allocated for feed costs. Making fermented silage feed is one alternative that can be used to overcome this problem. This community service program aims to improve the knowledge and skills of laying duck farmers in utilizing Azolla plants as fermented feed for ducks. This activity was carried out at the Soponyono 1 Farmer Group, Tanah Periuk Village, Muara Beliti District, Musi Rawas Regency, South Sumatra from July to September 2024. Extension activities were carried out through lectures and discussions on the potential of Azolla plants as alternative feed. Training activities were carried out through direct practice in processing Azolla plants into duck feed using silage fermentation technology. The results of this community service activity have been able to improve the knowledge and skills of the community in Tanah Priuk Village in processing Azolla plants into duck feed products that have economic value, so that they can reduce expenses on duck feed costs and increase duck productivity. The response of the socialization participants was generally good and positive; this can be seen based on the very high enthusiasm of the participants during the discussion session and also during the practice of making silage. After this community service activity is carried out, it is expected that the community service participants can make silage for animal feed independently.